Filmowiec nie może działać wyłącznie lokalnie. Z Krzysztofem Zanussim o współpracy z kinematografią niemiecką rozmawia Ewa Ciszewska - Zanussi, Krzysztof; Ciszewska, Ewa (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The paper presents an interview with Krzysztof Zanussi (born 17 June 1939), one of the most renowned award-winning Polish film directors. Some of his numerous films for television and cinema have been made in co-operation with German producers, including Manfred Durniok. His film Roads in the Night (Wege in der Nacht, 1979) was presented in 1980 in Cannes as part of the section “Un certain regard”. In Germany, Zanussi filmed not only some of his own screenplays, such as Imperative (Imperativ, 1982 – Special Jury Prize at the Venice International Film Festival in 1982), but also adaptations of Polish and German literature, for example House of Women (Haus der Frauen, 1977) based on a play by Zofia Nałkowska and Bluebeard (Blaubart, 1983) based on a novel by Max Frisch. In addition to those productions, he concurrently made films in Poland. Director of the TOR Film Studio since 1979. He produced films by such directors as Krzysztof Kieślowski and Agnieszka Holland. He currently works on a feature film entitled Ether.